The Strategy Of Managing Funds In Sports Clubs In The Light Of Professionalism. The Transfer Of Direct Public Support To The Support Of Public And Private Companies Field Study Conducted At The Level Of Some Of The Clubs Of The First Professional Associat - Mansouri Nabil; Lounas Abdellah . (sports creativity, 2025)
Abstract: The study aims to know the mechanism of collection and management of funds at professional Algerian clubs, especially with the beginning of the lack of public funding and methods of searching for private financing methods in the absence of a marketing culture for clubs and publicity for companies, In view of the fact that the current management of professional clubs in general is characterized by high performance ability, financial and administrative management as well as follow-up of the management of sports management and administrative movements require it to take a suitable place for integrated management and therefore it is imperative for administrators knowledge of modern scientific knowledge while choosing principles or Effective elements to achieve their desired objectives, This goal, which the Algerian clubs have been trying to achieve since the enactment of the laws of professional sports to be applied on the ground, both in terms of human management, administrative or financial. In light of this, our study came to clarify the most important strategies adopted by the Algerian professional clubs' managers in managing the funds from inputs and outputs and how they behave in light of the lack of government funding and what are the strategies for searching for funding sources for advertising and marketing, In the field of study, a sample of 40 Algerian clubs were used in the first excellent section and 40 clubs in the second excellent section. The questionnaire was designed for administrators as well as an interview with the heads of the sample study clubs. In light of the results obtained, the researchers recommended that: 1 - the actual application of the provisions of the law of professionalism to turn sports clubs into commercial enterprises in order to reduce the expenses of the state clubs. 2 - Dependence on marketing strategy and marketing in order to bring money to clubs 3 - Roofing the wages of players and advertising with the social security in order to reduce the waste of money